Entrepreneurship Contemporary Issues - Turuk, Mladen (IntechOpen, 2021)
Entrepreneurship plays an exceptional role in the development of economies and is a vital source of change in all aspects of society. This book tries to facilitate a fundamental rethinking of entrepreneurial activity and how it is manifested. It addresses a critical shortcoming in much of the research, education, and economic development work that deals with entrepreneurship. Instead of the general theories of entrepreneurship, the book lays a foundation for developing theories of different kinds of entrepreneurial ventures. As the reader navigates these pages, he or she should hopefully broaden their entrepreneurial landscape and identify critical factors that drive contemporary entrepreneurship.